Analysis of Smart Tourism in the Mandalika Special Economic Zone - Lestanata, Yudhi; Hidayatullah, Hidayatullah; Daaris, Yuli Yanti; Kurniawan, Cahyadi; Muhammad, Rio Eza Nur; Putri, Nadila (REFORMASI, 2024)
This study aims to examine the phenomenon of smart tourism in the Mandalika Special Economic Zone. The research methodology used in this study is descriptive qualitative, using secondary data obtained from websites, the internet, and related literature. The findings of the study indicate that smart tourism indicators such as Smart Accessibility in the Mandalika Special Economic Zone have several accesses issued by the government such as the Go Mandalika website where tourists can later access access through the website then the Ayo Ke Lombok application, Ayo Ke Lombok is a digital platform that provides a complete guide to enjoy various attractive offers in Lombok, including accommodation, location, tourist attractions, culinary, and much more. The next topic is the halal tourism application. The attraction of Lombok Sumbawa, then Smart Ads in the Mandalika Special Economic Zone through the Go Mandalika website on the Central Lombok Regency booklet which explains and displays several advertisements showing activities, culinary, transportation. The Go Mandalika website provides information about health services, festivals, and events in the Mandalika Special Economic Zone. This website also displays various interesting tourist attractions available in the area. This website serves as a practical reference for tourists who wish to explore the various tourist locations in the Mandalika special economic zone, including cultural, natural and man-made attractions.Penelitian ini bertujuan untuk mengkaji fenomena pariwisata cerdas di Kawasan Ekonomi Khusus Mandalika. Metodologi penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif, dengan menggunakan data sekunder yang diperoleh dari situs web, internet, dan literatur terkait. Temuan penelitian menunjukkan bahwa indikator smart tpourism seperti Smart Accessibility in kawasan ekonomi Khusus mandalika memiliki beberapa akses yang dikeluarkan pemerintah seperti website go mandalika yang dimana wisatawan nntinya bisa mengakses akses melalui website tersebut kemudian aplikasi ayo ke lombok, Ayo Ke Lombok merupakan platform digital yang menyediakan panduan lengkap untuk menikmati berbagai penawaran menarik di Lombok, termasuk akomodasi, lokasi, objek wisata, kuliner, dan masih banyak lagi. Topik berikutnya adalah aplikasi wisata halal. Daya tarik Lombok Sumbawa, selanjutnya smart Ads pada kawasan ekonomi khusus mandalika melalui website go mandalika pada booklate kabupaten lombok tengah yang di mna di jelaskan dan ditampilkan beberapa iklan yang menunjukan aktifitas, kuliner, transportasiSitus web Go Mandalika menyediakan informasi tentang layanan kesehatan, festival, dan acara di kawasan ekonomi khusus Mandalika. Situs web ini juga menampilkan berbagai objek wisata menarik yang tersedia di kawasan tersebut. Situs web ini berfungsi sebagai referensi praktis bagi wisatawan yang ingin menjelajahi berbagai lokasi wisata di kawasan ekonomi khusus Mandalika, termasuk objek wisata budaya, alam, dan buatan